The consultation relationship as a complex partnership: experiences of psychological consultation in Atlantis - Maw, Anastasia (Department of Psychology, 2023)
Community psychology has as its fundamental aim the wish to make mental health care more accessible, applicable and practicable to a greater number of people. In the South African context with its history of the inequitable distribution of mental health services and the shortage in resources to meet the needs of the majority, this is a particularly salient issue. Consultation has been suggested as a way of sharing psychological skills with front line mental health workers. The literature on consultation, however, is limited in its understanding of the complex interplay of power dynamics between the consultant and consultee, and the effects of this on the aims and goals of the consultation relationship. In this study a comparative, qualitative analysis of consultation with a school nurse and a mental health worker in Atlantis is discussed. Atlantis, a coloured town situated 48 kilometres from Cape Town along the west coast, is a remnant of Apartheid's separate development policy. A thematic analysis of the consultation relationships highlights the complex interplay of culture, race, class, language, gender and 'goodness of fit' between consultant and consultee in the consultation partnership. Recommendations are made regarding the use of needs assessment, the assessment of suitability of both consultant and consultee for consultation work, issues of power and empowerment and the goals and aims of the consultation partnership.